KUALITAS LABA DAN CORPORATE GOVERNANCE: BENARKAH KUALITAS LABA BANK SYARIAH LEBIH RENDAH DARI BANK KONVENSIONAL? - Laela, Sugiyarti Fatma (Jurnal Akuntansi dan Keuangan Indonesia, 2012)
Research regarding the association between corporate governance (CG) and the predictability of earning in Islamic bank is still limited. Islamic bank adopts profit loss sharing (PLS) instead of interest system as used by conventional bank. Regardless its benefit, PLS theoretically provides the potential of moral hazard which leads to opportunistic behaviors of managers. As a result, the quality of accounting information maybe decreases. This study examines the predictability of earning especially the ability of current earning to predict future cash flows using CG as a moderating variable. Using samples of Islamic and conventional banks from period of 2007- 2010 and least square method, this study finds that there is no strong evidence of earning predictability in the banking industry. The influence of current earning on future cash flow is not significant. However, the implementation of CG which measured by self-assessment scores, strengthen the association of current earning and future cash flows. The better the implementation of CG, the stronger the predictability of earning. This study also finds that the predictability of earning in Islamic bank is stronger than conventional bank, even though the impact of CG implementation on earning predictability for both types of bank is not different.